Maintain the Economic Activity of Subak in Social and Environmental Transformation - I Gusti Ayu Purnamawati; Gede Adi Yuniarta; Putu Ria Astria; Lucy Sri Musmini (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aimed to determine the effect of economic sustainability and social capital on the sustainability of traditional irrigation management in Bali. This quantitative research method uses primary data obtained from questionnaire data and measured by a Likert scale. The population of this study was 2,726 subak members in the province of Bali, and the research sample obtained a sample of 348 people. Questionnaires, as research data were collected and distributed to each member of the subak and statistical or data analysis techniques in the study, were considered using the Structural Equation Model (SEM) with WarpPLS 7.0 software modeling. The results of this study indicate that economic sustainability and social capital have a positive and significant impact on the sustainability of traditional irrigation management in Bali.